Sabhara Unit Patrol Efforts in Preventing Criminal Acts of Theft in the Jurisdiction of Garut Police - Daksa, Muhammad Anugrah Perdana (Police Studies Review, 2024)
The problem of poverty and unemployment can affect the stability of national security, one of which is crime. Every month the reports that come in Garut Resort Police in the form of motor vehicle theft fluctuate so that it requires close attention. The Sabhara Unit carries out its duties professionally. In this case the Sabhara Unit is the front guard in carrying out patrol duties. The purpose of this study is to describe the implementation of Sabhara unit patrols in preventing criminal acts of motor theft, factors that inhibit and support the Sabhara Unit patrol and what efforts have been made by Sabhara Unit patrols. This research uses a qualitative approach with the type of descriptive qualitative research. The location of this research took place in Garut Regional Police Station, West Java. Data collection techniques using interviews, document studies and observations. In analyzing data, data reduction, data presentation and conclusion drawing are carried out. The results of this study reveal that the Garut Police Sabhara unit has carried out systematic stages, but in the planning, organizing, and controlling stages did not run optimally, the factors that support the Sabhara unit's performance are the long-standing experience of serving members. For the inhibiting factor is the quality of personnel is still lacking. Garut Resort Police has efforts to increase patrol efforts to prevent motor vehicle theft using the Strong Point method, but it has not been carried out maximally because in the active implementation of Strong Point only utilizing four wheels does not utilize two wheels which impacts cannot reach places community housing that is prone to motor vehicle theft.